2021
DOI: 10.1126/sciadv.abg7444
|View full text |Cite
|
Sign up to set email alerts
|

The H3K36me2 writer-reader dependency in H3K27M-DIPG

Abstract: Histone H3K27M is a driving mutation in diffuse intrinsic pontine glioma (DIPG), a deadly pediatric brain tumor. H3K27M reshapes the epigenome through a global inhibition of PRC2 catalytic activity and displacement of H3K27me2/3, promoting oncogenesis of DIPG. As a consequence, a histone modification H3K36me2, antagonistic to H3K27me2/3, is aberrantly elevated. Here, we investigate the role of H3K36me2 in H3K27M-DIPG by tackling its upstream catalyzing enzymes (writers) and downstream binding factors (readers)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Our observation that knockdown of HRP2, as well as JPO2, robustly abrogated the survival, clonogenicity, and tumorsphere formation capacity of DTX-resistant cells implicates for the first time these proteins in the survival of chemoresistant PCa cells. These results are consistent with recent studies showing that depletion of LEDGF/p75 sensitizes mixed-lineage leukemic cells to chemoresistance and that individual or combined silencing of LEDGF/p75 and HRP2 reduces the in vivo growth of treatment-resistant glioma [15,62].…”
Section: Discussionsupporting
confidence: 93%
“…Our observation that knockdown of HRP2, as well as JPO2, robustly abrogated the survival, clonogenicity, and tumorsphere formation capacity of DTX-resistant cells implicates for the first time these proteins in the survival of chemoresistant PCa cells. These results are consistent with recent studies showing that depletion of LEDGF/p75 sensitizes mixed-lineage leukemic cells to chemoresistance and that individual or combined silencing of LEDGF/p75 and HRP2 reduces the in vivo growth of treatment-resistant glioma [15,62].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies evaluating H3K36me2 observed inconsistent results for recruiting DNMT3A and shaping the intergenic DNA methylation landscape [ 19 ]. Moreover, H3K36me2 could demarcate PRC2-mediated H3K27me2 and H3K27me3 domains in ESCs [ 20 , 21 ]. However, the functions of H3K36me2 in piPSCs and TSCs are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…NSD2 overexpression is linked with tumor aggressiveness [ 96 ] in cancers of the breast [ 97 ], cervix [ 98 ], lung [ 99 ], kidney [ 100 ], head and neck [ 101 ], brain [ 91 ], blood [ 102 ], colorectum [ 103 ], prostate, skin [ 96 ], and ovary [ 24 ]. Carcinogenesis associated with changes in the expression of NSD2 is also linked with cell cycle dysregulation [ 102 ], VEGF-A-mediated angiogenesis [ 104 ], hematopoietic stem cell differentiation [ 105 ], metastasis [ 91 ], chemoresistance (in osteosarcoma) [ 106 ], and the expression of various oncogenes (e.g., SYK , PTPN13 and ETV5 in multiple myeloma) [ 107 ].…”
Section: Histone H3k36 Di-methyl Transferasesmentioning
confidence: 99%
“…NSD2 overexpression is linked with tumor aggressiveness [ 96 ] in cancers of the breast [ 97 ], cervix [ 98 ], lung [ 99 ], kidney [ 100 ], head and neck [ 101 ], brain [ 91 ], blood [ 102 ], colorectum [ 103 ], prostate, skin [ 96 ], and ovary [ 24 ]. Carcinogenesis associated with changes in the expression of NSD2 is also linked with cell cycle dysregulation [ 102 ], VEGF-A-mediated angiogenesis [ 104 ], hematopoietic stem cell differentiation [ 105 ], metastasis [ 91 ], chemoresistance (in osteosarcoma) [ 106 ], and the expression of various oncogenes (e.g., SYK , PTPN13 and ETV5 in multiple myeloma) [ 107 ]. Gain-of-function mutations (E1099K and T1150A) in the SET domain of NSD2 have been associated with the enhanced enzymatic activity of NSD2 in mantle cell lymphoma and pediatric acute lymphoblastic leukemia, in which they cause destabilization of the auto-inhibitory loop responsible for keeping signaling in check (refer below) [ 108 , 109 ].…”
Section: Histone H3k36 Di-methyl Transferasesmentioning
confidence: 99%